Seasonal intensity-duration-frequency relationships for Pelotas, Rio Grande do Sul, Brazil - Emanuele B. Manke; Claudia F. A. Teixeira-Gandra; Rita de C. F. Damé; André B. Nunes; Maria C. C. Chagas Neta; Roberta M. Karsburg (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Although several studies have evaluated the intensity-duration-frequency relationships of extreme rainfall events, these relationships under different seasonal conditions remain relatively unknown. Thus, this study aimed to determine whether the intensity-duration-frequency relationships obtained seasonally from the rainfall records in the winter and summer represent the maximum rainfall events for the city of Pelotas, Rio Grande do Sul state, Brazil. Pluviographic data from 1982 to 2015 were used to create two seasonal series: one for the summer from December 21 to March 20 and the other for the winter from June 21 to September 22. These seasonal relationships were compared with the annual pluviographic data. The intensity, duration, and frequency relationships obtained from the summer rain data adequately represented the maximum rainfall in Pelotas, Rio Grande do Sul state, Brazil. The maximum intensity values of rainfall obtained from the relationship of intensity, duration, and frequency for the winter did not adequately encapsulate the occurrence of rain with greater intensities.